Association between blood pressure and the risk of biopsy-induced endobronchial hemorrhage during bronchoscopy - Saibin Wang; Qian Ye (BMC Pulmonary Medicine, 2022)
Abstract Background Hemorrhage is one of the most common complications of bronchoscopy. Although several hemorrhage risk factors have been proposed, it remains unclear whether blood pressure affects the onset of biopsy-induced endobronchial hemorrhage. Methods We conducted a retrospective cohort study of 643 consecutive adults with lung cancer over an approximately 4-year period (from January 2014 to February 2018) at a large tertiary care hospital. Patients were divided into the hemorrhage group and the non-hemorrhage group based on endobronchial biopsy (EBB) findings. The association between systolic pressure (SP), diastolic pressure (DP), mean arterial pressure (MAP), pulse pressure (PP), PP to DP ratio (PP/DP) and the risk of EBB-induced hemorrhage was evaluated using multivariate regression analysis and smooth curve fitting adjusted for potential confounding factors. Results The EBB-induced bleeding incidence was 37.8% (243/643) in our cohort. An independent association was found between PP/PD and the EBB-induced hemorrhage risk (per 1 SD, adjusted odds ratio, 0.788; 95% confidence interval, 0.653-0.951). The multivariate regression analysis performed using quartiles of PP/DP revealed that lower level of PP/DP ratio was related to a higher risk of EBB-induced hemorrhage (P for trend <0.05) after adjustment for potential confounders. However, no association was observed between SP, DP, MAP, PP and EBB-induced hemorrhage. Conclusions Low PP/DP was the independent risk factor for biopsy-induced endobronchial hemorrhage during bronchoscopy in patients with lung cancer.